Plano-convex lens type CsPb2Br5-CsPbBr3 composite micron disc and preparation method thereof

The planoconvex lens-type CsPb2Br5-CsPbBr3 composite microdisk was prepared by chemical vapor deposition, which solved the problem of poor stability of CsPbX3 perovskite nanocrystals, achieved controllable growth and improved optical performance of composite microdisks, and was suitable for lasers and optical imaging and other fields.

CN119640394APending Publication Date: 2025-03-18GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411807028.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the stability of all-inorganic CsPbX3 perovskite nanocrystals, resulting in problems such as phase conversion and decomposition under external conditions, limiting its application in lasers and other fields.

Method used

The planoconvex lens-type CsPb2Br5-CsPbBr3 composite microdisk was prepared by chemical vapor deposition. The diameter and center thickness of the microdisk were controlled to achieve its controllable growth using uniform mixing of CsBr and PbBr2 and the high-temperature growth reaction in a tube furnace.

Benefits of technology

The prepared CsPb2Br5-CsPbBr3 composite microdisk has better crystal quality, excellent optical performance and is suitable for large-scale production, and can be used in lasers with tunable cavity length and optical imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640394A_ABST
    Figure CN119640394A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite nanocrystalline materials, and particularly relates to a plano-convex lens type CsPb2Br5-CsPbBr3 composite micron disc and a preparation method thereof. In order to develop the growth-controllable CsPb2Br5-CsPbBr3 composite material, a chemical vapor deposition method is utilized, CsBr and PbBr2 are uniformly mixed and placed in the center of a tubular furnace, a silicon substrate is placed in the downstream of the tubular furnace, inert gas is introduced, and after a high-temperature growth reaction, the growth-controllable CsPb2Br5-CsPbBr3 composite material is prepared. And the CsPb2Br5-CsPbBr3 composite micron disc with a smooth surface and a plano-convex lens type appearance is obtained on the silicon substrate by controlling a proper cooling temperature. According to the method for preparing the CsPb2Br5-CsPbBr3 composite material, the needed raw materials are easy to obtain, the preparation process is simple, the method is suitable for large-scale production, and the prepared plano-convex lens type CsPb2Br5-CsPbBr3 composite micron disc is excellent and controllable in optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite nanocrystalline materials, and specifically relates to a plano-convex lens type CsPb2Br5-CsPbBr3 composite micron disk and a preparation method thereof. Background Art

[0002] All-inorganic CsPbX3 (X = Cl, Br, I) perovskite materials have the characteristics of tunable wavelength, narrow half-peak width, low laser threshold and spectral coherence, high fluorescence quantum efficiency, long carrier diffusion length, high luminescence efficiency, etc. It is a semiconductor material with excellent performance and a very potential laser gain medium. It has broad application prospects in the fields of solar cells, light-emitting diodes, lasers, photoelectric detection and backlight display. The band gap of CsPbX3 perovskite materials is tunable. When the halide composition of CsPbX3 changes between Cl, Br or I, its photoluminescence peak wavelength can be adjusted between 410-700nm, and wavelength-adjustable lasers can be prepared. Therefore, perovskite materials have bright application prospects in lasers.

[0003] Although all-inorganic CsPbX3 perovskite materials have excellent optical properties, due to their poor stability, under the influence of external conditions (temperature, humidity, polar solvents), CsPbX3 nanocrystals face problems such as phase transformation, decomposition, agglomeration and oxidation, which leads to an increase in the laser threshold of lasers using CsPbX3 as a working material, greatly limiting the application of CsPbX3 perovskites in lasers and other fields. In order to solve the above problems, researchers have proposed a variety of methods to improve the stability of CsPbX3 perovskite nanocrystals. Among them, the most studied is to coat the surface of CsPbX3 perovskite nanocrystals, coating them inside a more stable shell to improve their resistance to the external environment. Common coating materials mainly include polymers, inorganic substances, porous materials, heterojunctions, etc. In the current surface coating method, ligands are mainly added to the solution during the formation of CsPbX3 to passivate vacancy defects in CsPbX3 nanocrystals, such as lead vacancies and halogen vacancies. However, due to the existence of complex operation and unstable growth results, the preparation cost is high and it is not conducive to large-scale production. Current research shows that among the three halide perovskites, CsPbBr3 is more stable than CsPbCl3 and CsPbI3. CsPb2Br5 is a byproduct that is easily formed in the process of preparing CsPbBr3 using CsBr and PbBr2 as raw materials, and CsPb2Br5 has better water and thermal stability than CsPbBr3. It not only retains the excellent photoelectric properties of CsPbBr3, but also enhances its stability. It has great application potential in the field of optoelectronics. Therefore, CsPb2Br5-CsPbBr3 composite materials have attracted widespread attention from researchers, and it is expected to use the CsPb2Br5-CsPbBr3 composite structure to improve the stability of CsPbBr3. However, there is currently a lack of a method for preparing CsPb2Br5-CsPbBr3 composite materials with controllable growth. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention uses a chemical vapor deposition method to prepare a plano-convex lens-type CsPb2Br5-CsPbBr3 composite microdisk with a smooth surface and significant Newton ring fringes, thereby achieving the controllable growth of the plano-convex lens-type CsPb2Br5-CsPbBr3 composite microdisk, and the diameter and center thickness of the microdisk are controllable.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk, the method comprising the following steps:

[0007] S1, mixing CsBr and PbBr2 and grinding them to obtain a powdered reactant raw material;

[0008] S2, the powdered reactant raw materials obtained in S1 are weighed and placed in the center of the tube furnace, and the silicon substrate is placed downstream of the tube furnace, and vacuum is drawn and inert gas is introduced;

[0009] S3. Adjust the flow rate of inert gas, control the pressure of the tube furnace to 40-70 torr, and set the temperature of the tube furnace to 550-610°C to start the growth reaction, then cool to 300-480°C to end the growth, take out the sample, and obtain a CsPb2Br5-CsPbBr3 composite micron disk with a smooth surface.

[0010] The present invention uses a chemical vapor deposition method to control the growth parameters to prepare a plano-convex lens type CsPb2Br5-CsPbBr3 composite material with controllable growth, and the chemical vapor deposition method prepares the sample at a high temperature, and the obtained composite material has better crystal quality. At the same time, the method for preparing the CsPb2Br5-CsPbBr3 composite material of the present invention has easy-to-obtain raw materials, a simple preparation process, and is suitable for large-scale production. The obtained plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk has excellent and controllable optical properties.

[0011] Preferably, in S3, the temperature of the tube furnace is 575-590° C., and the growth reaction time is 30 min.

[0012] Preferably, in S3, the heating rate of the tube furnace is 15-25°C / min.

[0013] Preferably, in S3, the growth is terminated after cooling to 440-460°C.

[0014] Preferably, the molar ratio of CsBr to PbBr2 in S1 is 1:1.

[0015] Preferably, in S2, the total mass of the powdered reactant raw material is 0.02-0.08 g. The diameter and center thickness of the micron disk can be adjusted by controlling the mass of the reactant raw material.

[0016] Preferably, in S2, 100-200 sccm of inert gas is introduced for a maintenance time of 20 min-1 h.

[0017] Preferably, in S3, the flow rate of the inert gas is adjusted to 10-25 sccm.

[0018] Preferably, in S3, the pressure of the tube furnace is controlled to be 50 torr.

[0019] Preferably, in S1, the grinding time is more than 1 hour.

[0020] Preferably, in S2, in order to make the gas flow in the growth area stable and the reactant concentration controllable, the silicon substrate is placed on an inverted corundum boat and placed downstream of the tube furnace.

[0021] The second aspect of the present invention provides a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micron disk prepared by the preparation method described in the first aspect, wherein the micron disk has a plano-convex lens morphology, a smooth surface, a thick center and a thin edge, the micron disk is solid, and has a diameter between 2-50um and a center thickness between 90-1000nm. The diameter and center thickness of the micron disk can be adjusted by adjusting the total amount of reactant raw materials and the position of the substrate; under an optical microscope, the micron disk exhibits interference phenomenon and colored Newton ring fringes appear. As the diameter and curvature of the micron disk increase, the number of Newton ring fringes increases and the fringes become denser.

[0022] Preferably, the photoluminescence (PL) peak of the micro-disk is between 510-520 nm.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention discloses a method for preparing a CsPb2Br5-CsPbBr3 composite micron disk with a plano-convex lens-shaped morphology. The method comprises the following steps: using a chemical vapor deposition method, uniformly mixing CsBr and PbBr2, placing the mixture in the center of a tube furnace, placing a silicon substrate downstream of the tube furnace, introducing argon gas, and after a high-temperature growth reaction, obtaining a CsPb2Br5-CsPbBr3 composite micron disk with a smooth surface and a plano-convex lens-shaped morphology on the silicon substrate by controlling the cooling temperature. Specifically, the present invention has the following advantages:

[0025] (1) The present invention adopts chemical vapor deposition method, by using small growth gas flow, small mass of reaction raw materials, and ensuring that the gas flow passes smoothly through the substrate area, strictly controlling the substrate position and other factors, to achieve the controllable growth of plano-convex lens type CsPb2Br5-CsPbBr3 composite micron disk, the diameter and center thickness of the micron disk are controllable.

[0026] (2) The raw materials required by the present invention are simple and easy to obtain, the reaction conditions and growth parameters are controllable, the operation is simple and efficient, and it is suitable for large-scale industrial production.

[0027] (3) The micron disk prepared by the present invention can be applied to lasers with tunable cavity length. In addition, this plano-convex lens type micron disk can be used to prepare CsPb2Br5-CsPbBr3 composite micron disk convex lens array by using the fixed-point growth method, which can be used in the fields of optical imaging, information processing and detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1-5Optical micrographs of the CsPb2Br5-CsPbBr3 composite micro-disks prepared in Examples 1-4 and Comparative Example 1, respectively;

[0029] Figure 6-8 The corresponding atomic force microscope (AFM) images and cross-diameter cross-section thickness distribution curves of three plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disks of different sizes and curvatures obtained using the growth conditions of Examples 1-3, respectively;

[0030] Fig. 9 This is the PL spectrum of the single plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk in Example 2. DETAILED DESCRIPTION

[0031] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0033] Example 1: A method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk

[0034] The preparation method comprises the following steps:

[0035] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0036] (2) Take 0.05 g of powdered reactant raw material and put it in a corundum ark (Tangshan Cuishitao Special Ceramics Factory, specifications: 60*30*15 mm), and then push the ark into the center of the tubular furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tubular furnace (20 cm from the center of the tubular furnace). Then, the tubular furnace is evacuated to vacuum, and 200 sccm of argon is introduced to maintain it for 20 minutes.

[0037] (3) The argon flow rate was adjusted to 15 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 575 °C. The temperature was raised to 575 °C at a heating rate of 21 °C / min. After reacting for 30 minutes, the mixture was cooled to 450 °C and taken out to obtain a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk.

[0038] The plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk prepared by the above preparation method has a plano-convex lens-type morphology, a smooth surface, a thick center and a thin edge, and a solid micro-disk. Most of the micro-disks have a diameter of about 25um, and some micro-disks with small diameters exist. The corresponding optical micrograph is shown in the figure. Figure 1 As shown, the micron disk exhibits significant Newton ring fringes. Figure 6 The AFM image and cross-diameter section thickness distribution curve corresponding to a single micron disk show that the surface of the micron disk is smooth, thick in the center and thin at the edge, and the center thickness is 295nm.

[0039] Example 2: Preparation method of a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk

[0040] The preparation method comprises the following steps:

[0041] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0042] (2) Take 0.03 g of powdered reactant raw material and put it in a corundum ark, then push the ark into the center of the tube furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tube furnace (20 cm from the center of the tube furnace). Then, the tube furnace is evacuated to vacuum and 200 sccm of argon is introduced to maintain it for 20 min.

[0043] (3) The argon flow rate was adjusted to 15 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 575 °C. The temperature was raised to 575 °C at a heating rate of 21 °C / min. After reacting for 30 minutes, the mixture was cooled to 450 °C and taken out to obtain a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk.

[0044] The grown plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk has a plano-convex lens morphology, a smooth surface, a thick center and a thin edge. The micro-disk is solid and the diameter is mainly distributed around 20um. The corresponding optical micrograph is shown in Figure 2 As shown, the micron disk exhibits significant Newton ring fringes. Since the amount of reactant raw materials used is less than that in Example 1, the size of the obtained micron disk is smaller and the number of Newton ring fringes is less than that in Example 1. Figure 7 The AFM image of a single micron disk and the thickness distribution curve of the cross-diameter section show that the micron disk has a smooth surface, thick center and thin edges. The center thickness is 200nm, and its diameter and thickness are both less than Figure 6The reduction in diameter and thickness is the direct reason why the number of Newton rings of the micro-disk in Example 2 is less than that of the micro-disk in Example 1. Fig. 9 This is the PL spectrum of a single micron disk prepared under the growth conditions of this embodiment. It can be seen that the micron disk has excellent luminescence performance.

[0045] Example 3: Preparation method of a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk

[0046] The preparation method comprises the following steps:

[0047] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0048] (2) Take 0.07 g of powdered reactant raw material and put it in a corundum ark, then push the ark into the center of the tube furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tube furnace (19.5 cm from the center of the tube furnace). Then, the tube furnace is evacuated to vacuum and 200 sccm of argon is introduced to maintain it for 20 min.

[0049] (3) The argon flow rate was adjusted to 15 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 575 °C. The temperature was raised to 575 °C at a heating rate of 21 °C / min. After reacting for 30 minutes, the mixture was cooled to 450 °C and taken out to obtain a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk.

[0050] The plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk prepared by the above preparation method has a plano-convex lens morphology, a smooth surface, a thick center and a thin edge, and a solid micro-disk. The diameter of the micro-disk prepared under this condition is mainly distributed between 20-35um. The corresponding optical micrograph is shown in FIG. Figure 3 As shown, the microdisk exhibits significant dense Newton ring fringes. Figure 8 The AFM image of a single micron disk and the thickness distribution curve of the cross-diameter section show that the surface of the micron disk is smooth, thick in the center and thin at the edge. The center thickness is 958nm, which is significantly higher than Figure 6 and Figure 7 The significant increase in thickness makes the curvature of the micro-disk prepared in this embodiment larger than that in Examples 1 and 2, resulting in denser Newton ring fringes than in Examples 1 and 2. It can be seen from this embodiment that by comprehensively adjusting the amount of reactant raw materials and the position of the substrate, the size and curvature of the micro-disk can be effectively adjusted, thereby adjusting the number and density of Newton ring fringes.

[0051] Example 4: Preparation method of a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk

[0052] The preparation method comprises the following steps:

[0053] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0054] (2) Take 0.08 g of powdered reactant raw material and put it in a corundum ark, then push the ark into the center of the tube furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tube furnace (20 cm from the center of the tube furnace). Then, the tube furnace is evacuated to vacuum and 100 sccm of argon is introduced to maintain it for 1 hour.

[0055] (3) The argon flow rate was adjusted to 15 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 575 °C. The temperature was raised to 575 °C at a heating rate of 21 °C / min. After reacting for 30 minutes, the mixture was cooled to 450 °C and taken out to obtain a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk.

[0056] The grown plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk has a plano-convex lens morphology, a smooth surface, a thick center and a thin edge. The micro-disk is solid and its diameter is mainly distributed between 20-50um. The corresponding optical micrograph is shown in Figure 4 As shown, the micro-disk exhibits significant Newton's ring fringes. Since the amount of the reactant raw materials is larger than that in Examples 1 and 2, the diameter of the obtained micro-disk is larger, and the number of Newton's ring fringes is greater than that in Examples 1 and 2.

[0057] It can be seen from Examples 1-4 that by comprehensively adjusting the amount of reactant raw materials and the position of the substrate, the diameter, thickness and curvature of the micron disk can be effectively adjusted, thereby adjusting the number and density of Newton ring fringes.

[0058] Example 5: Preparation method of a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk

[0059] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0060] (2) Take 0.02 g of powdered reactant raw material and put it in a corundum ark, then push the ark into the center of the tube furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tube furnace (20 cm from the center of the tube furnace). Then, the tube furnace is evacuated to vacuum and 200 sccm of argon is introduced to maintain it for 20 min.

[0061] (3) The argon flow rate was adjusted to 15 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 575°C. The temperature was raised to 575°C at a heating rate of 21°C / min. After reacting for 30 minutes, the mixture was cooled to 450°C and taken out. Similarly, a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk with a smooth surface and significant Newton ring fringes was prepared.

[0062] Example 6: Preparation method of a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk

[0063] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0064] (2) Take 0.05 g of powdered reactant raw material and put it in a corundum ark, then push the ark into the center of the tube furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tube furnace (20 cm from the center of the tube furnace). Then, the tube furnace is evacuated to vacuum and 200 sccm of argon is introduced to maintain it for 20 min.

[0065] (3) The argon flow rate was adjusted to 10 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 590°C, and the temperature was raised to 590°C at a heating rate of 21°C / min. After reacting for 30 minutes, the mixture was cooled to 450°C and taken out. Similarly, a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk with a smooth surface and significant Newton ring fringes was prepared. Comparative Example 1: A method for preparing a plano-convex lens-type CsPb2Br5-CsPbBr3 composite micro-disk

[0066] (1) In a glove box, CsBr and PbBr2 were mixed in a molar ratio of 1:1 and then ground in an agate mortar for more than one hour to obtain a powdered reactant raw material.

[0067] (2) Take 0.05 g of powdered reactant raw material and put it in a corundum ark, then push the ark into the center of the tube furnace. The silicon substrate is placed on the inverted corundum ark and pushed into the downstream of the tube furnace (20 cm from the center of the tube furnace). Then, the tube furnace is evacuated to vacuum and 200 sccm of argon is introduced to maintain it for 20 min.

[0068] (3) The argon flow rate was adjusted to 15 sccm, the pressure of the tube furnace was adjusted to 50 torr, and the center temperature of the tube furnace was set to 575 °C. The temperature was raised to 575 °C at a heating rate of 21 °C / min. After reacting for 30 minutes, the mixture was cooled to room temperature and taken out to obtain a plano-convex lens-type CsPb2Br5-CsPbBr3 composite microdisk.

[0069] The difference from Examples 1-6 is that in Comparative Example 1, the sample is taken out after cooling to room temperature. Compared with the micro-disk taken out after cooling to 450°C, the surface of the grown micro-disk is very rough. The corresponding optical micrograph is as follows: Figure 5 As shown in the figure, the Newton ring fringes of the micrometer disk become blurred. It can be seen that by controlling the cooling method, the effect of controlling the surface flatness of the sample is achieved.

[0070] In summary, the CsPb2Br5-CsPbBr3 composite micro-disk obtained by the above-mentioned preparation method of the present invention has a smooth surface, a plano-convex lens-shaped morphology, a thick center and a thin edge, and the micro-disk is solid; the diameter, center thickness and curvature of the micro-disk can be adjusted by adjusting the total amount of reactant raw materials and the position of the substrate, the diameter is between 2-50um, and the center thickness is between 90-1000nm; the surface flatness of the micro-disk can be regulated by cooling. Under an optical microscope, the micro-disk exhibits interference phenomenon and colorful Newton ring fringes appear; and as the diameter and curvature of the micro-disk increase, the number of Newton ring fringes increases and the fringes become denser. The photoluminescence (PL) peak of the micro-disk is between 510-520nm.

[0071] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk, characterized in that: The following steps are involved: S1, mixing CsBr and PbBr2 and grinding them to obtain a powdered reactant raw material; S2, the powdered reactant raw materials obtained in S1 are weighed and placed in the center of the tube furnace, and the silicon substrate is placed downstream of the tube furnace, and vacuum is drawn and inert gas is introduced; S3. Adjust the flow rate of inert gas, control the pressure of the tube furnace to 40-70 torr, and set the temperature of the tube furnace to 550-610°C to start the growth reaction, then cool to 300-480°C to end the growth, take out the sample, and obtain a CsPb2Br5-CsPbBr3 composite micron disk with a smooth surface.

2. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S3, the temperature of the tube furnace is 575-590°C, and the growth reaction time is 30 minutes.

3. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S3, the heating rate of the tube furnace is 15-25°C / min.

4. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S3, the growth is terminated after cooling to 440-460°C.

5. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: The molar ratio of CsBr to PbBr2 in S1 is 1:

1.

6. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S2, the total mass of the powdered reactant raw materials is 0.02-0.08 g.

7. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S2, 100-200 sccm of inert gas is introduced and maintained for 20 min-1 h.

8. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S3, the inert gas flow rate is adjusted to 10-25 sccm.

9. The method for preparing a plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk according to claim 1, characterized in that: In S1, the grinding time is 1 hour or longer.

10. A plano-convex lens type CsPb2Br5-CsPbBr3 composite micro-disk prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The micron disk has a plano-convex lens shape, a smooth surface, a thick center and a thin edge. The micron disk is solid, has a diameter between 2-50um, and a center thickness between 90-1000nm. The diameter and center thickness of the micron disk can be adjusted by adjusting the total amount of reactant raw materials and the position of the substrate. Under an optical microscope, the micron disk exhibits interference phenomenon and colorful Newton ring fringes appear. As the diameter and curvature of the micron disk increase, the number of Newton ring fringes increases and the fringes become denser. The photoluminescence peak of the micron disk is between 510-520nm.